1996
DOI: 10.1007/bf02346127
|View full text |Cite
|
Sign up to set email alerts
|

Étude anatomique de la vascularisation des tendons des muscles de la coiffe des rotateurs de l'épaule

Abstract: The aim of this study was a better understanding of the role of the vascular supply as a pathogenic factor in rotator cuff disease. Twenty-five shoulders from unembalmed cadavers were studied after injection of the upper limb aa. with barium sulfate. The predominant arteries were the vessels of the subscapularis m. These branches originated from the axillary a. the anterior circumflex humeral a., and the posterior circumflex humeral a. The supraspinatus m. was supplied by the suprascapular a. but the acromial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 15 publications
0
45
0
3
Order By: Relevance
“…This classic description has been reported by many authors (Maral et al, 1993;Determe et al, 1996;Abrassart et al, 2006;Standring et al). Determe et al, observed that the suprascapular artery supplied the supraspinatus muscle.…”
Section: Introductionmentioning
confidence: 64%
“…This classic description has been reported by many authors (Maral et al, 1993;Determe et al, 1996;Abrassart et al, 2006;Standring et al). Determe et al, observed that the suprascapular artery supplied the supraspinatus muscle.…”
Section: Introductionmentioning
confidence: 64%
“…Intrinsic system situated at the musculo-tendinous junction, intrinsic system located at the osteo-tendinous junction and the extrinsic system via the paratenon or synovial sheath. As the principal arterial source of the supraspinatus muscle-tendon complex, the suprascapular artery ramifies within the muscular belly to convey an anastomotic network across the musculotendinous junction to supply the distal portions of the supraspinatus tendon (Moseley & Goldie, 1963;Ling et al;Determe et al;Standring et al;Naidoo et al, 2014). …”
Section: Naidoo N; Lazarus L and Satyapal K Smentioning
confidence: 99%
“…Subsequently, authors have described it as being hypovascular (Codman;Macnab, 1973;Lohr & Uhthoff, 1990;Brooks et al, 1992;Determe et al, 1996;Kane et al, 2006;Adler et al, 2008;Levy et al, 2008), avascular (Rathburn & Macnab;Herberts et al, 1981;Ling et al, 1990;Chansky & Iannotti) or hypervascular (Seitz et al) (Table I). Barr (2004) postulated avascularity to arise from the compression and attrition of the supraspinatus tendon in a narrowed subacromial space.…”
Section: Introductionmentioning
confidence: 99%
“…A funkcionális kapillárissűrűség csökken a sérült izomrész közelében [11]. Cadavervizsgálatban egy relatív hypovascularizált részt (critical zone) találtak a supraspinatus izom tapadásától 8 mm-re, amely megfelel a szakadások leggyakoribb predilekciós helyének [12].…”
Section: Megbeszélésunclassified